Factors associated with knowledge and awareness of stroke in the Iraqi population: a cross-sectional study - Al-Obaidi, Hala; Khidhair, Zainab; Jirjees, Feras; Barakat, Muna; AlSalamat, Husam; Kharaba, Zelal; Alfoteih, Yassen; Haddad, Chadia; Mansour, Sara; Hallit, Souheil; Malaeb, Diana; Hosseini, Hassan (Frontiers in Neurology, 2023)
Stroke is a highly prevalent condition with high rates of death and disability in Iraq and worldwide. Knowledge of stroke and its associated risk factors is essential for disease prevention and rapid response when confronted with a stroke patient. This study aimed o assess stroke knowledge and identify factors associated with awareness among the general Iraqi public. A questionnaire-based, cross-sectional survey was carried out on the Iraqi population. The self-administered online questionnaire contained three sections. The study got ethical approval from the Research Ethics Committee at the University of Baghdad.The results showed that knowledge regarding the identification of all risk factors was reported in 26.8% of the participants. In addition, 18.4% and 34.8% of the participants recognized all symptoms, and mentioned all possible consequences of stroke respectively. Previous medical history with chronic diseases had important relationships with the response when faced with a person having an acute stroke. In addition, there was a significant relationship between males and smoking people and identification of early symptoms of stroke. In conclusion, there was a lack of knowledge about risk factors for stroke among the participants. There is a need for an awareness program among the Iraqi people to raise their knowledge of stroke that can impact the reduction of stroke mortality and morbidity.